2007
DOI: 10.1093/ndt/gfm530
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glomerular heparan sulphate domains in murine and human lupus nephritis

Abstract: Background. Recently, we identified specific N-and 6-O-sulphated heparan sulphate (HS) domains on activated glomerular endothelial cells. In this study, we evaluated in lupus nephritis the expression of different HS domains on glomerular endothelium and in the glomerular basement membrane (GBM). Methods. The expression of specific glomerular HS domains and the presence of immunoglobulins (Ig) were determined by immunofluorescence staining of kidney sections of patients with nephritis due to systemic lupus eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…One may wonder why colocalization of chromatin or experimental anti‐dsDNA antibody probes with laminin was not found. This can be explained by the hypothesis that laminin within the electron‐dense deposits is masked by chromatin–immune complexes, and therefore not accessible to antilaminin antibodies, similar to the situation described for HS (45). Elution of chromatin–antibody complexes should lead to the reappearance of laminin, as we showed recently for glomerular HS in lupus‐prone mice and patients with SLE (45).…”
Section: In Vivo–bound Nephritogenic Autoantibodies In Lupus Nephritimentioning
confidence: 90%
See 3 more Smart Citations
“…One may wonder why colocalization of chromatin or experimental anti‐dsDNA antibody probes with laminin was not found. This can be explained by the hypothesis that laminin within the electron‐dense deposits is masked by chromatin–immune complexes, and therefore not accessible to antilaminin antibodies, similar to the situation described for HS (45). Elution of chromatin–antibody complexes should lead to the reappearance of laminin, as we showed recently for glomerular HS in lupus‐prone mice and patients with SLE (45).…”
Section: In Vivo–bound Nephritogenic Autoantibodies In Lupus Nephritimentioning
confidence: 90%
“…This can be explained by the hypothesis that laminin within the electron‐dense deposits is masked by chromatin–immune complexes, and therefore not accessible to antilaminin antibodies, similar to the situation described for HS (45). Elution of chromatin–antibody complexes should lead to the reappearance of laminin, as we showed recently for glomerular HS in lupus‐prone mice and patients with SLE (45). Recent findings with regard to the glomerular targeting of autoantibodies in lupus nephritis are graphically summarized in Figure 1.…”
Section: In Vivo–bound Nephritogenic Autoantibodies In Lupus Nephritimentioning
confidence: 90%
See 2 more Smart Citations
“…[13][14][15] A deficiency of a-mannosidase II (aM-II), which is associated with branching in N-glycans, has been found to induce human SLE-like glomerular nephritis in a mouse model. 16 Green et al reported that branching structures of N-glycan in mammals are involved in protection against immune responses in autoimmune disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%